Housing space quality towards quality of life: a case study of double storey terrace houses - Abu Bakar, Aniza; Abdul Malek, Nurhayati; Mohit, Mohamad Abdul; Othman, Rosniza; Sanusi, Aliyah Nur Zafirah (EDP Sciences, 2016)
The success of every housing area is determined by its user satisfaction level, living there. The quality of the house, its spaces within the unit, housing neighbourhood and green open space can directly influence the quality of life. Limitation of space following high land cost in urban area, evaluation of the housing environment as a whole including the green open space needs to be studied as it affects the residents’ satisfaction level. This study concentrates on spaces within a housing area to evaluate the residents’ level of satisfaction of the Taman Melati Mastika (TMM), Kuala Lumpur and to understand how they perceived their quality of life through the housing environment and the availability of green open space. Thus, this research was carried out through site observation and analysis, and self-administered questionnaire survey. 247 questionnaire surveys were distributed to the residents of TMM and (n=62) responded. When focused on the housing unit, this study provides an insight on the types of outdoor spaces (front yard-front lane and backyard-back lane) and their elements and utilization, and quality of housing spaces toward users’ quality of life in TMM, Kuala Lumpur. On the green open space, the assessment of quality of life is based on three factors that are the safety level of the neighbourhood and park, health issues related to housing environment and park as well as the satisfaction on the housing amenities and park facilities. The result of this study suggests that the residents are satisfied with the existing spaces within their compound and adjacent to it and this lead towards the overall satisfaction living in the area. The quality of space and good utilization of housing areas can lead towards better quality of life in the Terrace housing area is confirmed.